2022
DOI: 10.2147/ndt.s374416
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postoperative Cognitive Dysfunction Following Inhalational vs Total Intravenous General Anesthesia: A Systematic Review and Meta-Analysis

Abstract: Postoperative cognitive dysfunction (POCD) has been increasingly recognized as a contributor to postoperative complications. A consensus-working group recommended that POCD should be distinguished between delayed cognitive recovery, ie, evaluations up to 30 days postoperative, and neurocognitive disorder, ie, assessments performed between 30 days and 12 months after surgery. Additionally, the choice of the anesthetic, either inhalational or total intravenous anesthesia (TIVA) and its effect on the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A time interval of 4-8 weeks was chosen for which the postoperative tests could be taken. This was because the incidence of postoperative neurocognitive disorders at one postoperative month is almost identical to that at three postoperative months [31,35], but it is possible that a small group of patients suffered from transient cognitive decline not diagnosed before postoperative testing. The incidence of postoperative neurocognitive disorders could therefore have been underestimated.…”
Section: Pre-operative Montrealmentioning
confidence: 99%
“…A time interval of 4-8 weeks was chosen for which the postoperative tests could be taken. This was because the incidence of postoperative neurocognitive disorders at one postoperative month is almost identical to that at three postoperative months [31,35], but it is possible that a small group of patients suffered from transient cognitive decline not diagnosed before postoperative testing. The incidence of postoperative neurocognitive disorders could therefore have been underestimated.…”
Section: Pre-operative Montrealmentioning
confidence: 99%
“…[4,6,8,11,16] Postoperative cognitive dysfunction refers to changes in orientation, thinking, memory, attention, and other cognitive abilities in patients undergoing surgical anesthesia who have no preoperative psychiatric abnormalities. [17] The occurrence of postoperative cognitive dysfunction can impair recovery, prolong hospital stay and even affect the quality of life after discharge. [18,19] The elderly and the anesthesia technology are independent risk factors for the occurrence of postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effects of propofol on cognitive function warrant further study. Although propofol anesthesia may cause a certain degree of cognitive impairment in the short term, it is far less than inhalation anesthesia (Hou and Xiao, 2019;Negrini et al, 2022). A meta-analysis comparing the effects of propofol and sevoflurane anesthesia on the postoperative cognitive function of elderly patients with lung cancer (>60 years old) suggested that propofol yields more adverse effects on the cognitive function of elderly patients with lung cancer than sevoflurane (Sun et al, 2019).…”
Section: Propofolmentioning
confidence: 99%